Psychological impact on healthcare workers in obstetrics and gynecology in France in 18 French University Hospitals during the first Covid-19 lockdown: a prospective observational study. (2nd October 2022) - Chene, Gautier; Nohuz, Erdogan; Cerruto, Emanuele; Moret, Stéphanie; Atallah, Anthony; Saoud, Mohamed; ,
Abstract: Purpose: To assess the level of stress and anxiety in healthcare workers in the departments of obstetrics and gynecology in France during and after the first Covid-19 lockdown. Methods: Two web-based cross-sectional surveys using several validated questionnaires (the HAD scale, the PSS-10 questionnaire and the Short Form 12 Questionnaire [SF-12]) were proposed to all staff of obstetrics and gynecologic departments in 18 French university hospitals. Results: A total of 1565 respondents answered the first questionnaire and 1109 completed the second survey. Respondents reported greater levels of stress and impaired mental quality of life during the lockdown, followed by a significant improvement after the end of lockdown (respectively p < .0001 and p  = .01). Anxiety was significantly higher among the older participants during the lockdown ( p  = .008). The potential putative factors related to impaired mental health status were personal protective equipment (PPE) deficit (<.0001), the fear of contracting the virus from the workplace and transmitting to their families (<.0001) and concerns about information given by media and hospitals (<.0001). Conclusions: Understanding the heavy mental repercussions of the Covid-19 pandemic on healthcare workers could lead to the identification of high-risk in medical and non-medical staff and the implementation of targeted psychological monitoring program.